Sympathetic skin response (SSR) in pediatric Guillain–Barré syndrome - Jin, Mei; Liu, Jing; Liu, Kang; Zhao, Libo; Zhao, Ziwei; Sun, Suzhen (Frontiers in Neurology, 2023)
Introduction In the present study, sympathetic skin response (SSR) characteristics were explored in children with Guillain–Barré syndrome (GBS) and the value of early diagnosis and prognostic evaluation in GBS complicated by autonomic dysfunction (AD) was evaluated. Methods A total of 25 children with GBS and 30 healthy controls (HCs) were enrolled in this prospective study. SSR findings for the two groups were compared. SSR and nerve conduction study (NCS) results were compared among patients with GBS, and differences in clinical characteristics between the groups with abnormal and normal SSR were analyzed. Results Within the GBS group, six patients (24%) required mechanical ventilation, 17 patients (66.7%) had AD, 18 patients (72%) had an abnormal SSR, and 13 patients (52%) had AD combined with SSR abnormalities. There was a statistically significant difference in SSR latency in the lower limbs between the GBS group and HCs (P < 0.05). There was no statistically significant difference between SSR and NCS results in the acute phase of GBS (P > 0.05), and there was no significant difference in the rate of AD or in Hughes functional grade at nadir between the groups with abnormal and normal SSR (P>0.05). However, there was a statistically significant difference between the results of SSR and NCS tests during the recovery phase (P = 0.003). Abnormal SSR mainly occurred in cases of the acute inflammatory demyelinating polyradiculoneuropathy (AIDP) subtype. In addition, SSR was abnormal in all pediatric GBS patients with poor prognosis 1 month after onset of symptoms. Conclusion Two-thirds of the children with GBS have AD. SSR could be used for early diagnosis and follow-up of GBS and may also be helpful in evaluating disease severity and short-term prognosis.